Influence of growth stimulants on soybean productivity in the Northern Steppe of Ukraine - Shepilova, T.; Petrenko, D.; Leshchenko, S.; Vasylkovska, K.; Andreychenko, O. (Scientific Progress & Innovations, 2025)
In the steppe zone of Ukraine, soybean productivity is often determined by insufficient precipitation and high temperatures, which causes crop loss, and therefore there is a need to study the elements of technology using effective modern growth stimulants that increase plant resistance to adverse environmental factors, stimulate growth processes, enhance plant metabolism and realise genetic potential of new soybean varieties in difficult arid growing conditions. The aim of the research is to determine the effect of growth stimulants and seed inoculation on the development of plants of the mid-season soybean variety Azimuth in the northern Steppe of Ukraine. The task is to determine the effect of treatment of crops with preparations on leaf area, number of bulbils, plant height, and seed productivity of soybeans. The research was conducted in 2022–2024 in Kirovohrad region. The field experiment included two factors. Factor A (seed inoculation): 1). Control (without inoculation), 2). BioMag Soybean (2 l/t). Factor B (growth stimulants): 1) Control (no treatment), 2) Eraiz 1.5 l/ha, 3) Atonik Plus 0.2 l/ha, 4) Humifield 0.1 kg/ha, 5) Mars EL 0.5 l/ha. Seed inoculation was carried out on the day of sowing, and the crops were treated with growth stimulants in the phase of soybean budding. As a result of the research, it was found that the use of growth stimulants and the biological product contributed to an increase in the leaf area of plants, plant height and the number of bulbils. Inoculation of seeds with BioMag increased the leaf area of plants in the phase of bean formation by 36–67 cm2 compared to the control. Growth stimulants Humifield and Mars EL showed higher efficiency, where plant height increased by 4.9–8.4 cm. The use of the growth stimulant Mars EL with biological product BioMag increased the leaf area to the absolute control by 223 cm2 (25.1 %), plant height – by 11 cm (14.6 %), the number of bulbils – by 15.7 pcs (49.4 %), seed weight – by 1.93 g/plant (38.4 %). Under the influence of the growth stimulator Humifield with BioMag, the productivity increase was 3.7 c/ha, which is 18.1 %. Mars EL was more effective, with a yield increase of 4.2 c/ha, or 20.6 %. When using these preparations without seed inoculation, the yield increase was 2.4–2.8 c/ha, respectively.